Building Interprofessional Competencies Through a Collaborative Prescribing Activity With Osteopathic, Pharmacy, and Physician Assistant Students - Veronica Vernon; Brian W. Skinner; Patricia S. Devine; Lori Fauquher; Emily Young (Association of American Medical Colleges, 2024)
Introduction Medication errors can lead to significant adverse events. Nearly 50% of medication errors occur during the prescription-writing stage of the medication use process, and effective interprofessional collaboration and communication are key to reducing error in this process. Methods We developed a three-part, 60-minute, interprofessional education activity providing medical, physician assistant, and pharmacy students the opportunity to practice collegial interprofessional communication surrounding prescribing practices. Learners met virtually initially as a large group and divided into small groups facilitated by a health professional. Part 1 involved reviewing two prescriptions prepared by learners; part 2 was a discussion about the education, roles, and responsibilities of each profession; and part 3 focused on identifying prescription errors in examples provided by faculty. Students completed a post-pre survey measuring their perception of learning the Interprofessional Collaborative Competency Attainment Survey (ICCAS) areas. Results Of 317 participants (151 doctor of osteopathy, 68 master of physician assistant studies, and 98 doctor of pharmacy students), 286 completed the post-pre survey, for a 90% response rate. Students reported statistically significant (p < .001) increases in all 20 questions spanning the six ICCAS areas. Discussion The virtual format allowed multiple institutions to participate from various locations. It broadened the learners' experience by fostering interaction among those with varied perspectives and allowed collaboration between locations and programs that otherwise could not have participated. The activity introduced students to virtual collaboration and key telehealth skills, enhancing their confidence and familiarity with virtual interactions in a professional setting.